Decoding the Diagnosis: How Artificial Intelligence Empowers Patient Understanding - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The journey from symptoms to a definitive diagnosis can often feel like navigating a complex, opaque system. For patients, receiving a diagnosis is not the e...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning